A recently developed MRI scoring system for hand osteoarthritis: its application in a clinical setting. Issue 8 (August 2016) - Ramonda, Roberta; Favero, Marta; Vio, Stefania; Lacognata, Carmelo; Frallonardo, Paola; Belluzzi, Elisa; Campana, Carla; Lorenzin, Mariagrazia; Ortolan, Augusta; Angelini, Federico; Piccoli, Antonio; Oliviero, Francesca; et al.
Abstract This study aimed to apply the recently proposed Oslo hand osteoarthritis magnetic resonance imaging (MRI) scoring system to evaluate MRI findings in a cohort of patients affected by long-standing erosive hand osteoarthritis (EHOA). Eleven female EHOA patients (median 59 [interquartile range 62–52] years, disease duration 9.5 [interquartile range 13–3.75] years) underwent MRI (1.5 T) of the dominant hand, and synovitis, bone marrow lesions (BMLs), joint space narrowing, osteophytes, cysts, malalignment, and erosions were scored using the Oslo scoring system. Intra- and inter-reader reliability were assessed. The patients also underwent X-ray examination, and bone features were evaluated using the same scoring system. Pain and tenderness were assessed during a physical examination. Spearman's non-parametric test was used to analyze the correlations between variables. MRI intra- and inter-reader reliability were found between good and moderate for many features. No statistical differences were found between the radiographs and MRI with regard to detection of JSN, malalignment, and bone erosions. Synovitis was detected in 39.8 % of the 80 joints examined (in a mild form in 80 %), erosions were found in 51.1 %, and BMLs were identified in 20.5 and 23.9 % at the distal and the proximal side, respectively. BMLs at both the proximal and distal ends were correlated with tender joints (BML distalp = 0.0013, BML proximalp = 0.012). The presence of synovitis was correlated with tenderness (p = 0.004) and erosions at both the distal and proximal joints (p = 0.004). The presence of erosions correlated with tender joints (p < 0.01) and the mean visual analog scale (VAS) score (distalp = 0.03, proximalp = 0.01). Synovitis and BMLs were correlated with clinical symptoms in our patients affected with long-standing EHOA.